NPM1 mutations may be associated with adverse outcome in the setting of myeloid neoplasms with complex karyotype. (December 2022) - Ramia de Cap, Maximiliano; Wu, Leo P.; Pihan, German A.; Narayanan, Damodaran; Morgan, Elizabeth A.; Pinkus, Geraldine S.; Cin, Paola Dal; Hurwitz, Stephanie N.; Bagg, Adam; Patel, Sanjay S.; Tam, Wayne; Ouseph, Madhu M.; et al.
Graphical Abstract: ga1 Highlights: Complex karyotype (CK) is associated with adverse outcome in myeloid neoplasms (MN) with NPM1 mutation. MN with CK and NPM1 mutation have similar outcomes to MN with CK and TP53 mutation. MN with NPM1 mutation and CK are not associated with prior cytotoxic therapy.